1987
DOI: 10.1002/j.1460-2075.1987.tb02657.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of the murine L-myc gene.

Abstract: We have isolated a 12 kb clone from the murine genome which we show by DNA transfection studies to contain an entire functional L‐myc gene and the transcriptional promoter sequences necessary for its expression. We have also isolated a 3.1 kb cDNA sequence from a murine brain cDNA library which corresponds to most of the L‐myc mRNA. We have identified the L‐myc coding region within the genomic clone by a combination of S1 nuclease analyses. Northern blotting analyses and comparative nucleotide sequence analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

1989
1989
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 40 publications
1
48
0
Order By: Relevance
“…L-zip encodes a mutant L-Myc protein with a deletion of amino acid residues 23-140. This construct was derived from the mouse L-myc cDNA (Legouy et al 1987). Both N-zip and L-zip are driven by the RSV/LTR and contain the SV40 polyadenylation signal described in c-zip.…”
Section: Materials and Methods Myc And Zip Expression Vectors And Thementioning
confidence: 99%
See 1 more Smart Citation
“…L-zip encodes a mutant L-Myc protein with a deletion of amino acid residues 23-140. This construct was derived from the mouse L-myc cDNA (Legouy et al 1987). Both N-zip and L-zip are driven by the RSV/LTR and contain the SV40 polyadenylation signal described in c-zip.…”
Section: Materials and Methods Myc And Zip Expression Vectors And Thementioning
confidence: 99%
“…early-passage REFs (Land et al 1983;Schwab et al 1985;Yancopoulos et al 1985;DePinho et al 1987a, b;Legouy et al 1987;Birrer et al 1988). In this assay, c-myc appears to be most oncogenically active, whereas N-myc and L-myc exhibit moderate and weak transforming activity, respectively (DePinho et al 1987a, b).…”
mentioning
confidence: 99%
“…The L-myc gene belongs to the myc family of proto-oncogenes and shares extensive sequence and functional homology with two other members of this intensely studied group, c-myc and N-myc (Nau et al 1985;Legouy et al 1987). Overexpression of all three genes has been associated with neoplasia and causes cell transformation (Boxer and Dang 2001;Lutz et al 2002;Pelengaris et al 2002;Strieder and Lutz 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Preparation of KNA and Northern blotting was as described (33). c-, hi-, and b,nyc probes and the probes specific for C# and VhJ558 have already been described (3,8,14,35,40). The Thy-1 probe is a 1.4-kb ApaI fragment isolated from the 3' untranslated region of the Thy-1 gene (41), thetis probe is a 1.3-kb fragment from the plasmid pros 1 (42).…”
Section: Molecular Analyses and Probes Preparation Of Genomic Dnamentioning
confidence: 99%
“…All three genes have a similar three-exon structure and encode nuclear phosphoproteins that contain several regions of extensive homology in their amino acid sequences (1). The conservation of the individual myc genes through evolution suggests that they exert unique but related functions (2)(3)(4)(5)(6). Several studies have shown that myc gene products are involved in the regulation of cellular proliferation and differentiation, but their exact function remains to be elucidated (1).…”
mentioning
confidence: 99%